Green Up! Sustainable Design Solutions for Healthier Work and Living Environments. - Famulari, Stevie (Milton : Productivity Press, 2019)
There are unique greening solutions and practices that help create a lifestyle shift, improving the health of living and working spaces for its occupants from a personal, business, environmental, and profitable perspective. Short-term and long-term considerations are important elements when moving forward towards healthy practices in lifestyles, choices, and site designs. This book addresses a myriad of greening practices that can be applied to structures in our urban, suburban, and rural cultures. From the loft to the neighborhood, the office spaces to the public spaces, and the schools to the communities, this book outlines how business owners and residents can integrate scale appropriate green solutions into their lifestyles. Green Up!: Sustainable Design Solutions for Healthier Work and Living Environments includes detailed illustrations and photographs to help you understand design opportunities for your space. Stevie Famulari provides unique insights and inspires business owners, residents, and planners to develop their own green understanding and design solutions. Illustrations and photographs of applied greening are included throughout the book to help inspire your own goals and design, and then transform them to reality. The author breaks down the misconceptions of the complexity of sustainability and green practices. Greening is a lifestyle change, and this step-by-step instruction guide lets you know how easy it is to transition to the green side!
The Green Design Can ImproveA Few Notes as You Enjoy your Greening Process; References; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Green Business; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Facility Management; Sustainable design; Sustainability; Buildings -- Environmental engineering